2021
DOI: 10.1186/s13287-021-02446-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects and potential applications of concentrated growth factor in dentin–pulp complex regeneration

Abstract: The dentin–pulp complex is essential for the long-term integrity and viability of teeth but it is susceptible to damage caused by external factors. Because traditional approaches for preserving the dentin–pulp complex have various limitations, there is a need for novel methods for dentin–pulp complex reconstruction. The development of stem cell-based tissue engineering has given rise to the possibility of combining dental stem cells with a tissue-reparative microenvironment to promote dentin–pulp complex regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…In the area of dentistry, (CGF) has several applications, including the dentin–pulp complex regeneration [ 48 ], defects of periodontium [ 37 ], alveolar osteitis treatment [ 27 ], ridge augmentation surgeries, recession coverage, sinus lift, cystectomy, mixed with autologous bone graft and also used as a membrane during dental implantation, etc [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the area of dentistry, (CGF) has several applications, including the dentin–pulp complex regeneration [ 48 ], defects of periodontium [ 37 ], alveolar osteitis treatment [ 27 ], ridge augmentation surgeries, recession coverage, sinus lift, cystectomy, mixed with autologous bone graft and also used as a membrane during dental implantation, etc [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggests that recently discovered concentrated growth factor can be used to stimulate proliferation and mineralization of dental pulp cells [ 83 ], in addition to its known ability modulate stemness and function in bone marrow stromal cells [ 156 ], periodontal ligament cells [ 157 ], DPSCs [ 158 ] and mesenchymal stem cells [ 156 ]. Concentrated growth factor, containing many important individual growth factors including PDGF, FDF, TGF-beta, VEGF and IGF, is known to impact many cell processes important in regenerative endodontics including adhesion, proliferation, migration, differentiation and local remodeling and angiogenesis [ [156] , [157] , [158] , [159] , [160] ]. In their study, Tian et al demonstrated concentrated growth factor could be used to improve the migration, proliferation and mineralization of dental pulp cells [ 83 ].…”
Section: Tooth Structurementioning
confidence: 99%
“…The authors noticed that BMP-2 is released slowly for at least 7 days in CGF and L-PRF. Finally, Li et al [127] summarized that CGF stimulates proliferation of different types of mesenchymal stem cells, including DPSCs, PDLSCs, as well as human mesenchymal stem cells (hTERT-E6/E7) in a dose-dependent manner.…”
Section: Mesenchymal Stem Cells and Platelet Concentratesmentioning
confidence: 99%